2017
DOI: 10.1007/s00706-017-1918-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved electroanalytical characteristics for flumetralin determination in the presence of surface active compound

Abstract: The use of square wave voltammetry (SWV) and square wave adsorptive stripping voltammetry (SWAdSV) in conjunction with a cyclic renewable silver amalgam film electrode for the determination of flumetralin is presented. Poor separation of two overlapped reduction peaks is significantly improved when hexadecyltrimethylammonium bromide is used as a component of the supporting electrolyte solution (together with BR buffer pH 9.5). The SW technique parameters were investigated and found optimal as follows: frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…GC electrode was purchased from BASi (USA), while AMFE [16] from MTM-Anko (Poland). Before measurements GCE was polished on abrasive paper with different meshes.…”
Section: Methodsmentioning
confidence: 99%
“…GC electrode was purchased from BASi (USA), while AMFE [16] from MTM-Anko (Poland). Before measurements GCE was polished on abrasive paper with different meshes.…”
Section: Methodsmentioning
confidence: 99%
“…In the next step, the possibility of separation of superimposed profluralin signals was examined. Various surfaceactive compounds were tested for this purpose (Guziejewski et al 2017). Better separation of peaks was achieved when cetyltrimethylammonium bromide was used.…”
Section: Preliminary Studiesmentioning
confidence: 99%
“…Very small consumption of silver amalgam not exceeding 10 μL and long-term stability with more than two thousand measurement cycles (Baś 2006;Piech et al 2008a) make this electrode design environmentally friendly and consistent with green chemistry demands. Excellent properties of silver amalgam film electrode have been successfully utilized in the determinations of metals (Baś 2006;Piech et al 2008a, b), vitamins (Baś et al 2011), drugs (Smajdor et al 2015;Smarzewska et al 2017a, b), hormones (Smajdor et al 2016a(Smajdor et al , 2017, steroids (Smajdor et al 2016b) and pesticides (Smarzewska et al 2017c;Guziejewski et al 2017Guziejewski et al , 2018. Initial experiments revealed a distinct electrochemical activity of the profluralin and enabled its determination at the glassy carbon electrode (Smarzewska et al 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…4 In aerobic soil, flumetralin is barely mobile; however, under anaerobic conditions, it decomposes with a 42-day half-life. 5 The Environmental Protection Agency has classified flumetralin as an almost non-toxic compound based on its high median lethal dose in white rats. 6 Researchers have reported that flumetralin exposure increases DNA damage in mice and humans.…”
Section: Introductionmentioning
confidence: 99%